2022
DOI: 10.3390/f13071046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation and Nitrogen Application on Soil Nutrients in Triploid Populus tomentosa Stands

Abstract: Irrigation and nitrogen application directly affect the availability and distribution of soil nutrients. Understanding the response of soil nutrients to long-term water–fertilizer coupling conditions is helpful to improve the management and use efficiency. Irrigation was divided into three gradient levels, which accounted for 45%, 60%, and 75% (W1, W2, and W3) of the field water holding capacity. Based on pure nitrogen, four levels of nitrogen application were set: 0.0, 101.6, 203.2, and 304.8 kg·hm−2 (N0, N1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…These findings demonstrated that when the application of nitrogenous fertilizer increased the N and P content of post-harvest soils also improved. Similar findings also documented by Zhang et al [20].…”
Section: Nitrogen Application Effect Soil Primary Nutrient Contentssupporting
confidence: 91%
“…These findings demonstrated that when the application of nitrogenous fertilizer increased the N and P content of post-harvest soils also improved. Similar findings also documented by Zhang et al [20].…”
Section: Nitrogen Application Effect Soil Primary Nutrient Contentssupporting
confidence: 91%
“…The soil nutrient content determines the state of plant growth and development and reflects the ability of the soil to provide nutrients to plants and improve environmental conditions [ 57 ]. Soil organic carbon is an important component of the soil and plays an important role in soil function and ecosystem value, and nitrogen addition can inhibit the microbial decomposition of plant-sourced organic matter inputs, as well as attenuate mineral adsorption by dead microbial residues, which can lead to changes in the carbon fraction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%